PENGEMBANGAN MODUL DIGITAL MATA PELAJARAN PRODUKTIF MULTIMEDIA KOMPETENSI DASAR MENGOPERASIKAN CLAPPERBOARD PADA KELAS XI JURUSAN MULTIMEDIA DI SMK NEGERI 2 KEDIRI - Helmi Zandra DN, Fauzia (Jurnal Mahasiswa Teknologi Pendidikan, 2017)
In materials operate clapperboard, SMKN 2 Kediri has one clapperboard to practice in learning. One clapperboard used for students and in one class 35 student is less effective for learning. Class XI students majoring in Multimedia N 2 Kediri many prefer to learn through the media, incline attention when the teacher explained face to face with the lecture method. In the Multimedia Lab SMKN 2 Kediri have supplied multiple units tablet for support learning activities. Learning teacher also expressed wish to be created by a media operate clapperboard learning materials to support learning. The purpose of this study is to produce a product in the form of digital media module. Digital module with Self Instructional characteristics that can function as a medium of self-learning. The model used is a model development Research and Development (R & D) in Sugiyono (2013). But in the process of development, researchers did not do mass production procedures. Researchers did not perform the procedure because of the development of mass production is directed to a class XII student of Multimedia Department of SMK Negeri 2 Kediri. Collection data methods used to test the feasibility of using the media poll to media experts, subject matter experts and learning experts. In this process the researchers used using the One-group pretest-posttest design. The results of the pretest-posttest that have been made are distributed in a T test with the results of t table = 11.58 table = 0.576, then tarithmetic > t table11.58> 0,.057. Resulting in significant changes in learning outcomes between pretest and posttest. This means that the development conducted by researchers effective to use the learning process. Keywords: Development, Digital Modul